An Architecture of Poetic Realism - Sebastian Schmaling (Oz, 2008)
At a time when the global design avant garde is infatuated with the possibilities of algorithmic form-making, when "retinal-based architecture" is a logical by-product of contemporary culture's opticentricity, and when virtual reality increasingly seems to trump actuality, our interest in hapticity, temporality, and architectural phenomenology may appear slightly archaic and out of step with contemporary thought.